Canyoning and Geotourism: Assessing Geosites for Canyoning Activites in Western Serbia - Tomić, Nemanja; Antić, Aleksandar; Tešić, Dajana; Đorđević, Tijana; Momčilović, Oliver (Turizam, 2021)
The aim of this research is to explore the current state and potential of Tribuća, Rača and Beli Rzav canyons for their further development as canyoning geotourism destinations in Western Serbia. This was done by applying the modified geosite assessment model (M-GAM) on the three analyzed canyons with special focus on values of importance for canyoning tourists. The results indicate that all three analyzed canyons possess significant natural values of great importance for the development of canyoning tourism, such as possibility for interpretation, representativeness, surrounding landscape and nature, protection level and current condition. The main issues are related to human induced elements such as promotional activities, interpretive tools and visitor centers. Given their importance for further tourism development, these activities should have priority in the future in order to attract a larger number of canyoning tourists to these geosites. Significant improvement of these elements along with improved promotional activities would bring more domestic as well as foreign tourists to these geosites which would benefit the local population and local economy through higher income and new jobs for the local community.